Avaliação da atividade do peptídeo antimicrobiano P34 frente a vírus patogênicos aos animais domésticos - Silva, Débora Scopel e (2013)
The development and use of drugs with the ability to prevent or strike an infection are indispensable for human and animal health. However, the antiviral drug arsenal is still small and has serious use restrictions, like small activity range, limited therapeutic usage and several degrees of cytotoxicity. The objective of this work was to evaluate the antiviral activity of an antibacterial peptide isolated from the intestinal contents of the fish Piau-com-pinta (Leporinus sp.), named P34. Its cytotoxicity was analyzed in different cell lineages, in order to evaluate its antiviral activity. This study was performed against viruses with different phenotypical and genotypical features like: canine adenovirus type 2 (CAV-2), canine coronavirus (CCoV), canine distemper virus (CDV), canine parvovirus type 2 (CPV-2), equine arteritis virus (EAV), equine influenza virus (EIV), feline calicivirus (FCV) and feline herpesvirus type 1 (FHV-1). It was observed antiviral activity, in vitro, against EAV and FHV-1, both enveloped viruses, with RNA e DNA genomes, respectively. A virucidal effect was observed when P34 was incubated for different periods of time with EAV at 37 °C. Transmission electronic microscopy analysis suggests that the peptide P34 binds and promotes lesions to the viral envelope. The peptide P34 does not have virucidal activity against FHV-1 and although its mechanism of action is not completely elucidated, it is possible to suppose that P34 interferes in the adsorption process of FHV-1. Thus, the peptide P34 may represent an antimicrobial substance with potential application in the prevention and treatment of viral infections caused by FHV-1 and EAV.